Deflection prediction of cantilever concrete beam using adaptive fuzzy inference system - Jepriani, Sujiati; ., Ibayasid; Prasetya Wibawa, Aji; Hernandez, Leonel (International Journal of Engineering and Technology, 2018)
The cantilever concrete beam is a beam made of concrete that is only supported or clamped at one end and the other end free or without the pedestal. The measure to which a structural member gets deviated from the initial position is called deflection. All the internal forces of cantilever beam serve to hold all the external forces due to the load so that the structure remains balanced. While the beam gets deflected under the loads, bending occurs in the same plane due to which stresses are developed. From the moment balance formula after integrated and solved with required boundary conditions, we get the downward deflection of beam. Fuzzy logic provides an inference structure that enables appropriate human reasoning capabilities. FIS (Fuzzy Inference System) is a system that processes the mapping formulation of a given input to produce an output using Fuzzy Logic. By using randomized data for all the variables of deflection formula within their respective ranges as training data, the FIS will be able to predict deflection of cantilever concrete beam after going through the training process adaptively.Â Â
Keywords: cantilever of concrete beam; deflection; Fuzzy Logic; FIS.